The potential role of T-cell metabolism-related molecules in chronic neuropathic pain after nerve injury: a narrative review - Dou, Xiaoke; Chen, Rui; Yang, Juexi; Dai, Maosha; Long, Junhao; Sun, Shujun; Lin, Yun (Frontiers in Immunology, 2023)
Neuropathic pain is a common type of chronic pain, primarily caused by peripheral nerve injury. Different T-cell subtypes play various roles in neuropathic pain caused by peripheral nerve damage. Peripheral nerve damage can lead to co-infiltration of neurons and other inflammatory cells, thereby altering the cellular microenvironment and affecting cellular metabolism. By elaborating on the above, we first relate chronic pain to T-cell energy metabolism. Then we summarize the molecules that have affected T-cell energy metabolism in the past five years and divide them into two categories. The first category could play a role in neuropathic pain, and we explain their roles in T-cell function and chronic pain, respectively. The second category has not yet been involved in neuropathic pain, and we focus on how they affect T-cell function by influencing T-cell metabolism. By discussing the above content, this review provides a reference for studying the direct relationship between chronic pain and T-cell metabolism and searching for potential therapeutic targets for the treatment of chronic pain on the level of T-cell energy metabolism.